Progress in science - Royer, B.F.S. (My University, 1895)
Introduction: As students of truth, we are not content with fact, but look through the telescope of reason to see what is before. And more commonly do we take a retrospective view that we may better know the present and contemplate the future. In childhood we are delighted with Grandpa’s stories, since he relates life so different from what we know it today. This makes it very pleasant to listen to him. The Scientist is even interested in these stories and in the changes that have been brought about, so that he sets to work to reveal some of the causes that make it possible for us to enjoy such different and varied opportunities that our fathers knew nothing about. But man himself has not changed. He is the same today as he was two thousand years ago.
Citation: Royer, B.F.S. Progress in science. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Progress; Science; Philosophy; Theses; Manuscripts (documents)